Interactions Between Microorganisms and Mineral Deposits: Implications for Corrosion of Metals - Diaz Mateus, Maria Alejandra (Curtin University, 2024)
Microbiologically influenced corrosion (MIC) is a major challenge in the oil and gas sector, responsible for 40% of pipeline corrosion. Despite extensive research on MIC, understanding its complexity in the presence of deposits remains limited, especially regarding under deposit microbial corrosion (UDMC). This study aims to deepen our understanding by investigating the interaction between deposits and microorganisms. Results highlight the crucial influence of deposit mineralogy and thickness on UDMC severity, offering insights for improved corrosion management practices in the hydrocarbon industry.